RELATION BETWEEN INTERNAL MIGRATION AND SOCIOECONOMIC DEVELOPMENT WITH INTER-REGIONAL INEQUALITY PERSPECTIVE: A CASE STUDY FROM TURKEY - Ciftci, Murat; Sengezer, Betul (YILDIZ TECHNICAL UNIV, 2015)
In this study it has been focused on the impact of inter-regional inequalities in terms of development for uncontrolled internal migration movement's finding a direction spreading throughout the country with expanding incrementally impact on starting from three large metropolis to the other secondary cities. The impact and power of influence on finding the direction of internal migration movement of Inter-regional inequality have been tested with the help of the functional relationship cause - effect relationship, discriminant analysis of identified methods. In the second stage, the sensitivity of those who migrated for the economic opportunities of provinces have been identified comparatively with the citizentry sensitivity as a comparative scala by Atkinson index approach. As a result of the statistical applications done by using discriminant analysis, it was determined that inter-regional economic development disparity was statistically significant for internal migration movements' finding direction but wasn't in the level reach practical significance. In other words, inter-regional development differences had the impact on migration places to be chosen but couldn't reach the power of influence predominantly in the statistically significant level. As a result of the statistical applications done by using the Atkinson index approach, it was encountered that the citizentry sensitivity in the provinces the immigrants would choose was much higher than the sensitivity of the economical opportunities.
Keywords: Regional science; regional economics; development economics; demography; regional inequality; internal migration movement.; Engineering